Analysis of Inventory Control Using Activity Based Costing Method at PT Liquid Kencana Abadi - Mendrofa, Minta Rohani; Zebua, Serniati; Mendrofa, Martha Surya Dinata; Sophia Molinda Kakisina (ProBisnis : Jurnal Manajemen, 2025)
This study aims to analyze the inventory control system at PT. Liquid Kencana Abadi and classify inventory items using the ABC analysis method. The research employed a quantitative descriptive approach, utilizing both primary and secondary data. Primary data were collected through interviews and observations with company employees, while secondary data were obtained from company records related to snack product sales between February and April 2025. The results revealed that the company’s inventory management was still inefficient, as it lacked a systematic inventory control method. Through ABC analysis, the inventory was categorized into three groups: Class A, consisting of fewer items with the highest contribution to inventory value; Class B, representing medium-value items; and Class C, comprising numerous items with relatively low contribution. Findings indicated that Class A accounted for the majority of the total inventory value, demanding stricter monitoring and procurement strategies. Consequently, ABC analysis proved to be an effective tool for improving efficiency, reducing unnecessary costs, and ensuring the availability of high-turnover items. This study highlights the importance of implementing systematic inventory control for business sustainability.